ANALISIS YURIDIS TERHADAP AKIBAT HUKUM PEMBATALAN AKTA JUAL BELI KARENA STATUS KEPEMILIKAN YANG TIDAK SAH (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 2514 K/Pdt/2019) - Rifda Karimah (Jurnal Perspektif Hukum, 2020)
The title of this research is "Juridical Analysis of the Legal Consequences of Cancellation of Sales and Purchase Deeds Due to Unauthorized Ownership (Study of the Supreme Court Decision Number 2514 K / Pdt / 2019)". Sale and purchase is an agreement in which the party who owns the land (the seller) binds himself to hand over his rights to the land which is subject to another party (the buyer). Transfer of land rights can not only be through buying and selling, exchanging, but can be through grants or because of inheritance. The problem that often arises as a result of grants is the lack of a Grant Deed owned by the grantee from the grantee, which then results in a dispute between the family of the donor and the recipient of the grant, especially the object being granted a piece of land. The land grant should have strong or valid evidence in this case the Grant Deed. Based on the results of the research, it is found that the legal protection to the injured party for the cancellation of the sale and purchase deed must be seen in the good faith of the parties in implementing the sale and purchase deed. If the sale and purchase deed is canceled and suffers a loss, it asks for compensation for costs purchased by the buyer in the context of purchase and delivery and can file compensation to the court. The cancellation of the sale and purchase deed made by PPAT is in accordance with the legal procedures in Government Regulation Number 10 of 1961 and Government Regulation Number 24 of 1997 concerning Land Registration. The legal consequences of the cancellation of grants and the cancellation of the land sale and purchase deed made by PPAT in the Supreme Court decision Number 2514 K / Pdt / 2019 were parties that were the legal consequences of the Supreme Court decision Number: 2514 K / Pdt / 2019 which were carried out against Defendant I and Defendant II jointly and severally paid the costs incurred in this case.